Standardization of fertigation schedule for rabi castor (Ricinus communis L.) under drip irrigation: Standardization of fertigation schedule for rabi castor (Ricinus communis L.) under drip irrigation - A V RAMANJANEYULU,; A MADHAVI,; M V NAGESH KUMAR,; T L NEELIMA,; M VENKATA RAMANA,; A SRINIVAS, (Journal of Oilseeds Research, 2020)
Fertigation @ 30 kg N during 10-55 days after sowing (DAS); 40-50 kg N during 56-85 DAS; 20-30 kg N during 86-115 DAS and 20 kg N/ha during 116-145 DAS resulted in significantly higher seed yield of castor (3351 to 3356 kg/ha), higher water use efficiency (8.79-8.82 kg/ha/mm) and nitrogen use efficiency (27.9 kg/ha).